(untitled) (Contemporary Journal of Social Science Review, 2025)
The concept of trade in Islam, including modern E-commerce, is firmly grounded in Islamic legal rulings, ethics, and commercial principles. E-commerce is considered permissible under Islamic law as it operates within the framework of trade contracts based on mutual consent, transparency, honesty, and the avoidance of prohibited practices such as usury, deception, monopoly, and gambling. Islamic jurisprudence holds that contracts, including electronic ones, are valid at all times and places as long as they meet Shariah conditions and there are no impediments. The trade must involve permissible goods and services and comply with ethical standards emphasizing integrity and fair dealings. This jurisprudential approach addresses electronic transactions, including those involving cards and credit systems, ensuring compliance with Islamic laws designed to protect interests and prevent harm. This research demonstrates that electronic network services and the receipt of legitimate commissions in E-commerce are permissible under Islamic law, provided that they are subject to conditions based on custom and juristic consensus. Electronic commercial sales and advertising are allowed if they abide by established Shariah conditions and approvals from contemporary jurisprudential councils. Specifically, credit cards have been jurisprudentially classified as permissible tools in E-commerce transactions, serving as commercial intermediation for a fee or agency with a fee, according to fatwas and scholarly opinions. Islamic Shariah protects E-commerce transactions through the protection of intellectual property rights and consumer rights, applying principles consistent with Islamic ethics. This protection includes deterrent penalties against violators, aligning with positive legal systems inspired by Shariah principles. Adherence to ethical standards such as honesty, transparency, and avoidance of prohibited practices remains a fundamental requirement. Electronic network service providers may charge a legitimate fee for services rendered under contracts like lease or agency, fully recognized in Islamic jurisprudence. Electronic commercial sales are valid when they comply with the rules of offer, acceptance, lawful objects, and mutual consent. Commercial advertising electronically is permissible if truthful, non-deceptive, and fulfills legal conditions. Credit cards in E-commerce are legally treated as agency or guarantee contracts, allowing a fee for intermediation using established rules confirmed by contemporary fatwas of Islamic Scholars.